POTENSI KELELAWAR SEBAGAI VEKTOR ZOONOSIS: INVESTIGASI BERDASARKAN KEANEKARAGAMAN JENIS DAN PERSEPSI MASYARAKAT TERHADAP KEBERADAAN KELELAWAR DI KOTA TANGERANG SELATAN - Wijayanti, Fahma; Humaerah, Armaeni Dwi; Fitriana, Narti; Dardiri, Ahmad (LPPM Universitas Negeri Jakarta, 2016)
Zoonosis from bats to human in urban areas is a problem that must be investigated.This study aims to determine the species diversity in Tangerang Selatan City and human perception of bats. The study was conducted in July 2015 to November 2015. Bats were caught by mist nets and harp traps. Traps was placed purposively based on bats traffic at each study site. There are 3 sampling locations, each location, has been done for 4 nights with 3 mist net. Bats are found in South Tangerang City consisting of 5 spicies, namely: Cynopterus brachyotis, Cynopterus horsfieldii, Cynopterus titthaecheilus, Macroglossus sobrinus and Myotis muricola, with an index of species diversity was (H ‘= 1.68). Human perception and behavior in relation to the spread of zoonosis are at high scores (> 75), which means that the perception of the bat can keep them away from a zoonotic disease caused by bat.